The embrace of unreason France, 1914 - 1940 - Brown, Frederick 1934- (Knopf, 2014)
"From acclaimed biographer and cultural historian, author of For the Soul of France ("Masterful history...hard to put down."-Henry Kissinger); Zola ("Magnificent." ...The New Yorker); andFlaubert ("Impeccable."-James Wood, cover, The New York Times Book Review)-a brilliant reconsideration of the events and the political, social, and religious movements that led to France's embrace of Fascism and anti-Semitism. Frederick Brown explores the tumultuous forces unleashed by the Dreyfus Affair, and examines how the clashing ideologies and the blood-soaked political scandals and artistic movements following the horror of World War I resulted in the country's era of militant authoritarianism; and how rioting, violent racism, and nationalistic fervor overtook France's sense of reason, sealed its fate, and led to the rise of the Vichy government. We see how the French intelligentsia turned away from the humanistic traditions and rationalistic ideals of the Enlightenment in favor of submission to authority that stressed patriotism, militarism, and xenophobia; how French conservatives attempted to rebuild and reshape the country's collective identity as the German threat loomed, as mistrust of the parliamentary Republic increased (a result of its illegal financial mismanagement of the building of the Panama Canal, and nostalgia for a monarchial government and the glories of wartime martyrdom); how the generation that came of age in the trenches, under fire, offered a new vision, and saw salvation in the surrender of reason to instinct. Brown masterfully brings to life Europe's-and France's-darkest modern years"..